2020
DOI: 10.3390/diagnostics10080548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronavirus Disease 2019 in Pulmonary Circulation. The Particular Scenario of Precapillary Pulmonary Hypertension

Abstract: The Coronavirus Disease of 2019 (COVID-19) has supposed a global health emergency affecting millions of people, with particular severity in the elderly and patients with previous comorbidities, especially those with cardiovascular disease. Patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) could represent an especially vulnerable population because of the high mortality rates reported for respiratory infections. However, the number of COVID-19 cases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 99 publications
(166 reference statements)
0
30
2
7
Order By: Relevance
“…Hemodynamic profiles in COVID-19 patients with ARDS are consistent with the elevated diastolic pulmonary gradient (the difference between the diastolic pulmonary artery pressure and the pulmonary artery wedge pressure) of >7 and pulmonary vascular resistance (PVR) >3 Wood units x m 2 , suggesting a pre-capillary type of PH [ 23 , 24 ]. RV dysfunction by elevated PVR is a poor prognostic factor in patients with COVID-19 [ 25 ].…”
Section: Management Of Preexisting or New-onset Ph Occurring With mentioning
confidence: 85%
“…Hemodynamic profiles in COVID-19 patients with ARDS are consistent with the elevated diastolic pulmonary gradient (the difference between the diastolic pulmonary artery pressure and the pulmonary artery wedge pressure) of >7 and pulmonary vascular resistance (PVR) >3 Wood units x m 2 , suggesting a pre-capillary type of PH [ 23 , 24 ]. RV dysfunction by elevated PVR is a poor prognostic factor in patients with COVID-19 [ 25 ].…”
Section: Management Of Preexisting or New-onset Ph Occurring With mentioning
confidence: 85%
“…A small survey and other COVID-19 PAH/CTEPH series reported to date [ 5 , 6 , 7 , 8 ] have suggested that COVID-19 has a relatively benign course in the setting of PAH and surprisingly favorable clinical outcomes. Postulated mechanisms for the presumed low risk for severe COVID-19 included protective effects of known low ACE2 levels in PAH, resulting in decreased viral entrance in the lung cells, mitigation from the COVID-19 cytokine storm afforded by the chronic inflammatory milieu of PAH, or theoretical (and controversial) hemodynamic beneficial effects on the ventilation/perfusion matching in COVID pneumonia/ARDS of specific PAH medication [ 5 , 6 , 7 , 8 , 9 ]. A larger survey of 58 pulmonary hypertension comprehensive centers in the US showed more sobering findings with an estimated hospitalization rate of PAH/CTEPH patients with recognized COVID-19 of 30% and mortality of 12%, which are worse outcomes compared to those in general population [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in published series to date, PAH patients that developed COVID-19 had seemingly favorable clinical outcomes [ 5 , 6 , 7 , 8 ]. Pathophysiologic mechanisms that could explain the paucity of reported cases and the surprisingly favorable outcomes of COVID-19 in patients with PAH and CTEPH have been reviewed in detail [ 9 ]. The chronic inflammatory status implicated in the pathobiology of pulmonary vascular remodeling in PAH, as well as the reduced expression ACE2 (the transmembrane receptor of the SARS-CoV-2 virus) in PAH might contribute to decreased cytokine storm and reduced viral entrance in PAH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH is hard to detect because its symptoms (e.g., shortness of breath, fatigue, and dizziness) are similar to those of other common non-life threatening conditions, and the official diagnosis for PAH must be made through invasive right heart catheterization [ 36 ]. Endothelial dysfunction is a common feature of patients with PAH and COVID-19 [ 37 , 38 ].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%